Clear cell carcinoma of the ovary: clinical profile and treatment outcomes-an experience from tertiary cancer centre in South India - S., Vino Anand; J., Kannan; D., Satheesh Kumar (International Journal of Research in Medical Sciences, 2024)
Background: Clear cell carcinoma of the ovary is a rare and aggressive subtype of epithelial ovarian cancer, accounting for approximately 5-10% of all ovarian malignancies. Characterized by unique histopathological features and a high degree of resistance to conventional platinum-based chemotherapy, its management is particularly challenging. This study aims to analyses the clinical profile, treatment modalities, and survival outcomes of 26 patients diagnosed and treated for clear cell carcinoma of the ovary at our institute, with the goal of identifying factors that contribute to improved prognosis and survival. Methods: We conducted a retrospective cohort study involving 26 patients diagnosed with clear cell carcinoma of the ovary between 2011 and 2020. Data on patient demographics, clinical presentation, treatment regimens, and survival outcomes were extracted from medical records. Statistical analysis included the using Kaplan-Meier survival curves to evaluate overall survival (OS) and progression-free survival (PFS). Results: The median age of the patients was 52 years, with 42.3% being premenopausal and 57% postmenopausal. Most common presentation were abdomen distension and abdomen pain/discomfort. Median overall survival of clear cell carcinoma was 36 months, and the median disease-free survival was 18 months. Early-stage diagnosis and optimal cytoreduction during surgery were associated with improved survival. Our findings highlight the importance of early detection and aggressive surgical management in improving outcomes for patients with clear cell carcinoma of the ovary. Conclusions: Clear cell carcinoma ovary relatively uncommon cancer. Patients diagnosed at an early stage demonstrated significantly better OS and PFS compared to those diagnosed at advanced stages. This study finding highlight the aggressive nature of this subtype and the critical importance of early detection and optimal surgical intervention. The study also underscores the challenge of chemo resistance in advanced-stage disease, emphasizing the need for innovative treatment strategies.